2015
DOI: 10.1016/j.jbiomech.2015.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of predicted muscle forces during gait to anatomical variability in musculotendon geometry

Abstract: Scaled generic musculoskeletal models are commonly used to drive dynamic simulations of motions. It is however, acknowledged that not accounting for variability in musculoskeletal geometry and musculotendon parameters may confound the simulation results, even when analysing control subjects. This study documents the three-dimensional anatomical variability of musculotendon origins and insertions of 33 lower limb muscles determined based on magnetic resonance imaging in six subjects. This anatomical variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…Whatever the approach used to identify the influential parameters, it seems important to analyse the evolution of the sensitivity measures or indices over the gait cycle as they may be different between the stance and swing phases or may vary with the joint amplitude, as it appears in the present study, depending on the knee flexion-extension. Some previous sensitivity analyses of a lower limb models have reported time averages [4,12,15,35,41], time integrals [9,29,43] as well as correlation coefficients [17,25,26,38] or root mean square differences [1] computed on the whole gait cycle. One study has reported partial derivatives of the output with respect to the parameters (calculated using a finite-difference approximations) at each instant of time of the gait cycle [36] and demonstrated varying influence of some parameters on the lower limb joint moments.…”
Section: Screening Methods and Sobol Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever the approach used to identify the influential parameters, it seems important to analyse the evolution of the sensitivity measures or indices over the gait cycle as they may be different between the stance and swing phases or may vary with the joint amplitude, as it appears in the present study, depending on the knee flexion-extension. Some previous sensitivity analyses of a lower limb models have reported time averages [4,12,15,35,41], time integrals [9,29,43] as well as correlation coefficients [17,25,26,38] or root mean square differences [1] computed on the whole gait cycle. One study has reported partial derivatives of the output with respect to the parameters (calculated using a finite-difference approximations) at each instant of time of the gait cycle [36] and demonstrated varying influence of some parameters on the lower limb joint moments.…”
Section: Screening Methods and Sobol Sensitivity Analysismentioning
confidence: 99%
“…The sensitivity analyses 1 Computer Methods in Biomechanics and Biomedical Engineering, 22:10, 925-935, 2019 were generally based on a Monte Carlo propagation of uncertainties and different ad hoc sensitivity indices. As far as gait analysis is concerned, the sensitivity is to be assessed at different instants of time and for numerous outputs (e.g., angles, moments) and that is why many indices involved time averages [4,12,15,35,41] or time integrals [9,29,43]. As a matter of fact, these sensitivity analyses have a high numerical cost which may also explain why only first order sensitivity indices, which give the expected reduction in the response variance by fixing one factor [32], have been used although non-linear effects and interactions between parameters can be of high importance [15].…”
Section: Introductionmentioning
confidence: 99%
“…First, the assumption that IC can be uniquely addressed to the plantar-flexors muscles (hence, excluding co-contraction of antagonist muscles 362 and neglecting the contribution of passive forces exerted by ligaments 366 ). Second, the accuracy of the estimated AT force strongly depends on the reliability of the collected experimental data (anatomical landmarks identification and skin artefact in the first place [367][368][369] ) and on the chosen musculoskeletal model (inertial parameters and musculoskeletal geometries are based on generic models scaled on the subject's proportions) 370 . For this latter reason, the scientific community has been recently focusing on the availability of imaging techniques to assess subject-specific musculoskeletal geometries simultaneously to motion data collection to estimate ankle dynamics [371][372][373] .…”
Section: : Outcome Evaluation Devices (Indirect Determination Of Acmentioning
confidence: 99%
“…However, this simplification had hardly an effect on the model outcomes, since these points have shown really low sensitivity . Similarly, low sensitivity of segment inertial parameters (Bosmans et al, 2015) ensure negligible effects of the linear scaling on the model predictions. The main limitation of the subject-specific models used in this study lies in the resolution and overall quality of the available medical images.…”
Section: 4 Discussionmentioning
confidence: 99%
“…For these complex applications, an accurate description of the musculoskeletal geometry is essential to obtain reliable model predictions. It is well known that inaccuracies in muscle-tendon (MT) moment arms (Hoy et al, 1990;Out et al, 1996;Maganaris, 2004), MT attachment sites and lines-of-action (Pal et al, 2007;Valente et al, 2014;Bosmans et al, 2015), and joint geometry (Martelli et al, 2015;Valente et al, 2015) affect model outcomes. Unfortunately, application of linear scaling laws to generic models (Delp et al, 1990;Klein Horsman et al, 2007;Arnold et al, 2010) cannot account for the inter-individual anatomical variability due to differences in age, height, weight and gender (White et al, 1989;Duda et al, 1996;Kepple et al, 1998).…”
Section: Introductionmentioning
confidence: 99%